THE INFLUENCE OF OFFICE MANAGEMENT ON PUBLIC SERVICES IN THE HILISALAWA'AHE DISTRICT OFFICE SOUTH NIAS REGENCY - Selateli Halawa; Odaligoziduhu Halawa; Robin Markus Putra Waruwu; Eliagus Telaumbanua (Jurnal Ilmiah METADATA, 2026)
At the Hilisalawa'ahe District Office, South Nias Regency, researchers found that administrative services to the public were not running optimally. The purpose of this study was to determine office management for public services at the Hilisalawa'ahe District Office, South Nias Regency. Data collection techniques were through observation and distribution of questionnaires to 33 employee and community respondents. Meanwhile, data analysis used validity tests, reliability tests, correlation coefficient analysis, determinant coefficient analysis, and hypothesis testing. In this study using quantitative research with data calculation using SPSS to obtain accurate values. The results of this study, the t test of variable X Quality management system is 17.257 with a significance level of 5% obtained t table of 2,034. It is known that the Sig value = 0.000 <0.05. So according to the interpretation: If the Sig value <0.05 or t count> t table then there is an influence between variable X on variable Y, conversely, If the Sig value> 0.05 or t count <t table then there is no influence between variable X on variable Y. So it can be concluded that the influence of office management is positive and significant on public services. In the calculation results the value of the determinant coefficient (R-Square) is 90.6%. For 9.4% is influenced by other factors not discussed in this study.